2016
DOI: 10.18869/acadpub.3dj.5.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Artifacts in Oral and Maxillofacial Histopathological Slides

Abstract: Introduction:One of the reasons that cause a pathologist to make an incorrect diagnosis includes artifacts leading to tissue changes and artificial structures in microscopic slides. The aim of this study was to examine the artifacts in histopathological slides in Zahedan School of Dentistry. Materials and Methods:In this cross-sectional study, all the available slides in Oral and Maxillofacial Pathology Archive at the School of Dentistry during 1999-2015 were evaluated for existing artifacts. The artifacts fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
3
2
1
Order By: Relevance
“…The formalin pigmentation is an artifact caused by the formalin fixation in acidic pH or environments with high temperature and humidity. Moreover, formalin pigmentation is more common in the tissues with high hemorrhage, and its frequency in the study of Saravani et al has been reported to be 90% (1), which is significant compared to the results of the present study. Microtomy is a tool used to cut the tissues for microscopic examination, and the formalin concentration, pollution, and long fixation time make it difficult to cut the samples.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The formalin pigmentation is an artifact caused by the formalin fixation in acidic pH or environments with high temperature and humidity. Moreover, formalin pigmentation is more common in the tissues with high hemorrhage, and its frequency in the study of Saravani et al has been reported to be 90% (1), which is significant compared to the results of the present study. Microtomy is a tool used to cut the tissues for microscopic examination, and the formalin concentration, pollution, and long fixation time make it difficult to cut the samples.…”
Section: Discussioncontrasting
confidence: 59%
“…According to the American Academy of the Oral and Maxillofacial Pathology, any abnormal tissue removed from the oral and maxillofacial area should be sent to a pathologist for evaluation and diagnosis (1). Biopsy plays an undeniable role in forensic medicine (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this research show a strong relationship between the concordance rate of histopathological and clinical diagnosis and the kind of lesion. This conclusion is comparable with those of Saravani et al [18,19] , who discovered a substantial relationship between the type of lesion (neoplastic or non-neoplastic) and clinicopathological concordance. Saravani et al [18] divided lesions into five main groups, with exophytic lesions being the most prevalent.…”
Section: Discussionsupporting
confidence: 91%
“…This conclusion is comparable with those of Saravani et al [18,19] , who discovered a substantial relationship between the type of lesion (neoplastic or non-neoplastic) and clinicopathological concordance. Saravani et al [18] divided lesions into five main groups, with exophytic lesions being the most prevalent. They also found that the occurrence of pigmented lesions was the lowest, while the concordance rates were greatest for white and scarlet lesions.…”
Section: Discussionsupporting
confidence: 91%